STATUS AND MANAGEMENT OPTIONS OF PHYTOPHTHORA INFESTANS, A CAUSAL AGENT OF THE LATE BLIGHT DISEASE OF TOMATO, IN TROPICAL AFRICA - R. I. Ndala P. A. Ndakidemi; E. R. Mbega . (Journal of Animal and Plant Sciences, 2019)
Late blight disease caused by Phytophthora infestans (Mont.) de Bary is a serious challenge in tomato (Solanum lycopersicum L or Lycopersicon esculentum L) production worldwide. In tropical Africa, the disease is increasing always due to its biology and different complex infection mechanism(s) used by its causative pathogen to survive, spread, and invade the tomato host plant and environment. Management options of the disease, such as integrated disease management (IPM), use of resistant tomato varieties, use of plant extracts and synthetic chemical pesticides have been recommended but are either poorly practised or limited in tropical Africa. Thus, this review discusses the status and commonly recommended management options against late blight disease-causing pathogen(s) including the pathogen strain complexes so that tomato growers and other stakeholders can understand specific strains and how they can design appropriate managerial approaches to halt challenges of the disease in tomato production in the tropical Africa.
Keywords: Host range; Pathogen infection Mechanism; Sign and Symptoms and Plant extract